Perception and satisfaction of diploma and degree students at University Technology MARA, Kota Kinabalu, Sabah towards implementation of 1Malaysia Book Voucher / Mohd Fareed Mohd Fuad and Mohd Aizuddin Munir Akbar - Mohd Fuad, Mohd Fareed; Munir Akbar, Mohd Aizuddin (2016)
This research is to show the perception and satisfaction of students towards 1Malaysia Book Voucher Programme with the purpose of the study is to determine the level of satisfaction and the perception of the programme between course level and family income groups. There have been several improvements made by the government regarding the 1Malaysia Book Voucher Programmes; however, some students did not utilise these incentives to buy books but rather exchange the vouchers for money for their personal use. This study covered diploma and degree students in University Technology MARA Cawangan Sabah. Crosssectional questionnaire survey is conducted as a research design. From the findings, most students have positive perception towards the implementation of BB1M by 68% of respondents. This illustrate, a sign of the programme gives a great impact to the student education. Overall the BB1M is a good initiative from the government for the students. There is no much difference in level of satisfaction between diploma and degree students while there are difference levels of satisfaction between high and low family income groups toward the 1Malaysia Book Voucher. This research shows there is a need for government to look into the account the grievance of students in term of the rules and regulation and made improvisation for better usefulness of 1Malaysia Book Voucher (BB1M).